Value of plasma AGEs and sRAGE expression in predicting the occurrence of ARDS in elderly COPD patients : AGEs and sRAGE expression in ARDS - Yu, Chen; Qichang, Lin; Zhimin, Zhang; Zhongqiang, Teng; Yanrui, Wang; Haiyan, Xie (Cellular and Molecular Biology, 2023)
This study aimed to explore the diagnostic value of advanced glycation end products (AGEs) and soluble receptors for advanced glycation end products (sRAGE) by detecting the expression levels of AGEs and sRAGE in the plasma of elderly patients with chronic obstructive pulmonary disease (COPD) combined with acute respiratory distress syndrome (ARDS). For this purpose, 110 COPD patients were divided into the elderly COPD group (n=95) and the elderly COPD combined with the ARDS group (n=15). An additional 100 healthy people were recruited as the control group. All patients were assessed with Acute Physiology and Chronic Health Evaluation (APACHE II score) after admission. The levels of AGEs and sRAGE in the plasma were measured by enzyme-linked immunosorbent assay. Results showed that compared with the elderly COPD group, the APACHE II score was significantly higher in the elderly COPD combined with ARDS group (P < 0.05); the level of plasma AGEs in the control group, the elderly COPD group, and the elderly COPD combined with ARDS group decreased in turn (P < 0.05), and the level of sRAGE increased in turn (P < 0.05). Pearson analysis exhibited that the plasma AGEs level was negatively correlated with the APACHE II score (r = -0.681, P < 0.05), and plasma sRAGE level was positively correlated with the APACHE II score (r = 0.653, P < 0.05). Binary Logistic analysis demonstrated that AGEs were the protective factor for ARDS in elderly COPD patients (P < 0.05), and sRAGE was the risk factor for ARDS in elderly COPD patients (P < 0.05). The areas under the curve of plasma AGEs, sRAGE, and their combination in the prediction of ARDS in elderly COPD patients were 0.860 (95%CI: 0.785-0.935), 0.756 (95%CI: 0.659-0.853), and 0.882 (95%CI: 0.813-0.951), respectively. The decreased level of AGEs and the increased level of sRAGE in the plasma of COPD patients with ARDS are associated with the disease severity and have a certain diagnostic value for ARDS in COPD patients, which may be potential markers for the clinical diagnosis of COPD combined with ARDS.